Standardized anthropological measurement of postcranial bones using three-dimensional models in CAD software. (September 2017) - Reynolds, Mikaela S.; MacGregor, Donna M.; Barry, Mark D.; Lottering, Nicolene; Schmutz, Beat; Wilson, Lance J.; Meredith, Matthew; Gregory, Laura S.
Highlights: Standardized virtual protocols to conduct linear skeletal measurements are needed. A standardized virtual protocol for linear skeletal measurements is introduced. Semi-automated anthropometric measurements using CAD software have high reliability. 3D virtual protocols have broad application to forensic anthropology. Abstract: This study introduces a standardized protocol for conducting linear measurements of postcranial skeletal elements using three-dimensional (3D) models constructed from post-mortem computed tomography (PMCT) scans. Using femoral DICOM datasets, reference planes were generated and plane-to-plane measurements were conducted on 3D surface rendered models. Bicondylar length, epicondylar breadth, anterior-posterior (AP) diameter, medial-lateral (ML) diameter and cortical area at the midshaft were measured by four observers to test the measurement error variance and observer agreement of the protocol (n = 6). Intra-observer error resulted in a mean relative technical error of measurement (%TEM) of 0.11 and an intraclass correlation coefficient (ICC) of 0.999 (CI = 0.998–1.000); inter-observer error resulted in a mean %TEM of 0.54 and ICC of 0.996 (CI = 0.979–1.000) for bicondylar length. Epicondylar breadth, AP diameter, ML diameter and cortical area also yielded minimal error. Precision testing demonstrated that the approach is highly repeatable and is recommended for implementation in anthropological investigation and research. This study exploits the benefits of virtual anthropology, introducing an innovative, standardized alternative to dry bone osteometric measurements.